Auxin Responsiveness of a Novel Cytochrome P450 in Rice Coleoptiles - Chaban, Christina (The American Society for Plant Biologists, 2003)
An early auxin-induced gene was isolated from rice (Oryza sativa L. subsp. japonica cv Nihonmasari) coleoptiles by a fluorescent-labeled differential display screen. The full-length gene contains conserved domains characteristic for the cytochrome P450 superfamily. This gene, designated as CYP87A3, was weakly expressed in dark-grown coleoptiles but was up-regulated rapidly and transiently when coleoptile segments were incubated in 5 μm indole-3-acetic acid. This induction by auxin could not be suppressed by cycloheximide. Depletion of segments from endogenous auxin reduced the amount of CYP87A3 transcripts. The CYP87A3 transcript level was rapidly, although transiently, up-regulated in response to light as well. The observed pattern of gene regulation might indicate a role in the suppression of auxin-induced coleoptile growth. The role of CYP87A3 is discussed with respect to auxin signaling in the regulation of coleoptile growth.